Abrasion Resistance of Paints Made with Curcumin Pigment and PVA Resin - FARIA Fernanda Cardoso de; SCHMID Aloísio Leoni; MIRANDA Isabela Pagani Heringer de (Architecture, Civil Engineering, Environment)
Polyvinyl acetate (PVA) polymer resins are commonly used in the manufacture of artisanal paints with natural inputs, giving them the classification of economic latex paint according to NBR 11702. Aiming to minimize the final cost, since PVA is the most expensive component, this study contributes to the area of building paints through the innovative idea of formulating paints with PVA resin, curcumin pigment extracted from the root of Curcuma Longa L., color preservative additives and bacterides, in order to find the appropriate proportions capable of reaching the minimum limit of resistance to abrasion, so that the paint is considered to have good performance according to technical standards. Furthermore, the present study analyzed the variation in the characteristics of the paints based on the variation in the amount of PVA in the mixtures. The results indicate that the addition of PVA at extreme levels reduces the abrasion resistance and viscosity of the mixtures. Statistical analysis obtained satisfactory results when PVA made up 33% of the emulsion. With the positive results, the present intention is to begin research in the area of building paints made with curcumin pigment and PVA as a binder.